Kelemahan Lembaga Keberatan Pajak - Budi Ispriyarso (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2019)
Abstract Tax disputes can occur between taxpayers or tax insurers with the government, among others because of differences in the amount of tax payable. One of the legal efforts that can be taken by taxpayers in the event of a tax dispute is an